Model Altman Z-Score Untuk Menganalisis Kejadian Kebangkrutan Perusahaan Peternakan Broiler X Di Kabupaten Malang - Novita Dewi Kristanti; Muhammad Ridho; Siti Azizah (Journal of Agriprecision & Social Impact, 2024)
The purpose of this study was to determine the causes of bankruptcy in broiler farms using the Altman Z-Score method using financial statements for the 2017-2019 period. This research was conducted from August to September 2021, this research was conducted by conductibf interviews with the Company Owner. The type of research used is descriptive quantitative research, namely by collecting, classifying, analyzing and interpreting the data obtained from the company so that it can provide an overview of the actual situation. The method used by researchers for data collection is by interview and documentation. The results showed how to overcome bankruptcy based on financial data, the company had total debt which was one of the causes of the company going bankrupt and another reason the company closed because in 2019 the price of chicken decreased. Factors causing the decline in broiler prices in 2019 were due to oversupply from broiler chickens, oversupply from Day Old Chicks (DOC), a decrease in people's purchasing power and distribution channels that were disrupted due to the issue of the cartel mafia.